A Novel Postbiotic From Lactobacillus rhamnosus GG With a Beneficial Effect on Intestinal Barrier Function - Gao, Jie; Li, Yubin; Wan, Yu; Hu, Tongtong; Liu, Liting; Yang, Shaojie; Gong, Zelong; Zeng, Qing; Wei, Yi; Yang, Weijun; Zeng, Zhijie; He, Xiaolong; et al. (Frontiers in Microbiology, 2019)
It has long been known that probiotics can be used to maintain intestinal homeostasis and treat a number of gastrointestinal disorders, but the underlying mechanism has remained obscure. Recently, increasing evidence supports that certain probiotic-derived components, such as bacteriocins, lipteichoic acids, surface layer protein and secreted protein, have the similar protective role on intestinal barrier function as the live probiotics. These bioactive components have been named ‘postbiotics’ in the most recent publications. We previously found that the Lactobacillus rhamnosus GG (LGG) culture supernatant is able to accelerate the maturation of neonatal intestinal defense and prevent neonatal rats from oral E. coli K1 infection. However, the identity of the bioactive constituents has not yet been determined. In this study, using liquid chromatography-tandem mass spectrometry analysis, we identified a novel secreted protein (named HM0539 here) involved in the beneficial effect of LGG culture supernatant. HM0539 was recombinated, purified and applied for exploring its potential bioactivity in vitro and in vivo. Our results showed that HM0539 exhibits potent protective effect on intestinal barrier, as reflected by enhancing intestinal mucin expression and prevent against lipopolysaccharide (LPS)- or tumor necrosis factor α (TNF-α)-induced intestinal barrier injury, including down-regulation of intestinal mucin (MUC2), zonula occludens-1 (ZO-1) and disruption of the intestinal integrity. Using neonatal rat model of E. coli K1 infection via the oral route, we verified that HM0539 is sufficient to promote development of neonatal intestinal defense and prevent against E. coli K1 pathogenesis. Moreover, we further extended the role of HM0539 and found it has potential to prevent dextran sulfate sodium (DSS)-induced colitis as well as LPS/D-galactosamine-induced bacterial translocation and liver injury. In conclusion, we identified a novel LGG postbiotic HM0539 which exerts a protective effect on intestinal barrier function. Our findings indicated that HM0539 has potential to become a useful agent for prevention and treatment of intestinal barrier dysfunction related diseases.